SPECIFIC FEATURES OF SYSTEM INFLAMMATORY RESPONSE SYNDROME AND NUTRITIONAL STATUS IN PULMONARY TUBERCULOSIS PATIENTS WITH CONCURRENT TYPE 1 AND 2 DIABETES - G. O. Kaminskaya; R. Yu. Abdullaev; O. G. Komissarova (Туберкулез и болезни лёгких)
45 pulmonary tuberculosis patients with concurrent type 1 diabetes, 69 pulmonary tuberculosis patients with concurrent type 2 diabetes and 131 pulmonary tuberculosis patients without diabetes (control group) were examined. The intensity of the system inflammatory response syndrome was evaluated by the markers of the acute inflammation phase – blood levels of C-reactive protein (CRP), serum amyloid A (SAA), α1 -antitrypsin (α1 -АТ), haptoglobin, and fibrinogen. Nutritional status was assessed by body mass index (BMI) and concentration of total protein (TP), albumin (A), and transthyretin (TTR). It was found out that in new progressing forms in pulmonary tuberculosis patients with concurrent diabetes the mobilisation of acute phase proteins responsible for early anti-infection protection (CRP, SAA) was less expressed compared to the patients without concurrent diabetes. On the contrary in torpent forms of the disease CRP and SAA were much higher in those with concurrent conditions compared to the patients without concurrent diabetes. The reaction of acute phase proteins in new cases and infiltrate and pneumonic forms of the disease was more severe in those with concurrent type 1 diabetes and more moderate and slow in case of type 2 diabetes. Nutritional status in the patients with concurrent conditions differed greatly from patients in the control group. With no concurrent diabetes all signs of nutritional deficiency (low BMI, A and TTR) promoted the severe course of the disease. TP remained within normal limits. Patients with concurrent diabetes demonstrated reduction TP and TTR, but BMI and A remained normal in case of type 1 diabetes and increased in type 2 diabetes. Ratio of albumins/globulins (A/G) went down in the control group but tended to increase in case of concurrent diabetes. According to correlation analysis the reduction of TP in the patients with concurrent condition was not due to A but globulins. Shifts fundamentally different for patients with concurrent diabetes and those without concurrent diabetes (increase of BMI, A, A/G) were much greater expressed in type 2 diabetes and manifestations of protein-energy deficiency (decrease of TP and TTR) were more intensive in type 1 diabetes.